Greece, the Eurozone Crisis and the Media: The Solution Is the Problem - Kaitatzi-Whitlock, Sophia (Javnost-The Public, 2014)
By October 2009, Greece faced a sovereign debt crisis and a borrowing crisis and it was said to be putting the Eurozone at risk. After much delay, the EU Commission together with the European Central Bank (ECB) and the IMF formed a hybrid tripartite entity, the so called “Troika,” to deal with the indebted country. This act raised the stakes since it converted the crisis to an issue of intense global media attention, influence and spin. The Greek people entered thus into the epicentre of a ferocious global publicness. This article analyses the Eurozone/Greek financial crisis, assessing critically the way that it was dealt with politically by national, European Union (EU) and Eurozone authorities. The author traces the modes that the eruption of the crisis was reported about, emphasising its crucial initial phase and exploring how crisis-management-policies were presented and discussed in transnational public spheres. She scrutinises the role of national and transnational media in framing this affair and key political communication manifestations or absence thereof. Moreover, the article examines the underlying material conditions and political economy motives of biased or “abnormal” reporting modalities. In terms of impacts, it elaborates on de-legitimation and polarisation of politics and in political communication of Greece as a consequence of “crisis management.” The article explores EU power relations and the tangle of socio-economic and political reactions/ events that evolved from a controversial “crisis management” model and their impacts to date.